Geography and the wealth of nations - Khalifa, Sherif (Lexington Books, 2022)
"In Geography and the Wealth of Nations, Sherif Khalifa argues that geography influences the factors that determine economic performance, such as the quality of institutions, the adopted cultural values, the systems of governance, the likelihood of conflict, the historical experiences, and the integration into the global economy"--